ANALISIS PUBLIC VALUE DALAM PELAYANAN PUBLIK PASAR BULU KOTA SEMARANG - Cindy Aulia Nikensy; Endang Larasati Setianingsih (Journal of Management and Public Policy, 2026)
Bulu Market is one of the traditional markets in Semarang City that has experienced improvements in service quality, but still faces various problems in the implementation of public services, such as suboptimal facilities, unmaintained cleanliness conditions, and a decrease in the number of active traders. This study aims to analyze the form of public value in public services at Bulu Market Semarang City and identify factors that drive the formation of public value. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. Data analysis is carried out in three stages: data reduction, data presentation, and conclusion drawing. The theory used is the concept of public value from Moore (1995) which includes three main dimensions: legitimacy and support, operational capacity, and public value outcomes. The results of the study indicate that Bulu Market services have a basis of legitimacy in the form of local regulations and support from the Semarang City Trade Office, but operational capacity is still not optimal, especially in terms of the availability of supporting facilities such as non functioning escalators and cleanliness management. In terms of substantial value, Bulu Market services have not fully provided economic, social, and ecological benefits that are felt by traders and visitors. Factors driving the formation of public value include clear regulations, management commitment to implementing technology-based levies, and vendor participation in market management. This study recommends improving the quality of physical facilities, optimizing service governance, and strengthening communication between market managers and service users to create sustainable public value.